FORMATION OF PERSONAL CULTURE OF MEDICAL UNIVERSITY STUDENTS - Kozachenko , Yuliia (Philological Treatises, 2023)
It is described the model of formation a medical student’s personal culture in the article. There are named three main fundamental foundations of a medical student. The theory of holism and therapeutic communication are determined as the basic aspects of communicative fundamental foundation. Cognitive theory, organization theory and critical thinking are defined as the part of motivational fundamental foundation. Social mentality and deontological model are named as the elements of valuable foundation. There are characterized normative, substantive and procedural aspects of a medical student’s personal culture formation. It is found out that main norms and official documents are an integral part of normative element. The list of skills is named for forming motivation, communicative skills and values of medical students. It is found out that one dimensional approach can be used for forming a medical student’s personal culture. The discipline “The basis of a personal development” is named as one of the ways to form and improve a medical student’s personal culture. It is determined that procedural aspect consists of different techniques, methods, principles, means, forms and approaches. The theoretical foundations of a medical student’s personal culture formation are determined. The basic ways of improvement a medical student’s personal culture are revealed. Tips are given on the use of basic techniques, methods, forms and means of forming a medical student’s personal culture.